http://www.aulamedica.es/fh/pdf/7860.pdf - Carmen Haro Márquez; Maria Rosa Cantudo Cuenca; Carmen Victoria Almeida González; Ramón Morillo Verdugo (Elsevier, 2015)
Purpose: To assess adherence and beliefs about long-term medicines for other chronic conditions among HIV-infected patients as well as to evaluate their relationship. Method: A cross-sectional study was conducted from may to july 2014 in HIV-infected patients treated with antiretroviral treatment (ART) and ≥1 long-term medicines for other chronic diseases. The variables analysed in the study were demographics: sex, age, education, employment status, living situation; clinical: mode of transmission, HIV plasma viral load ,T-CD4+, CDC classification; and pharmacotherapeutics: type of ART, adherence to long-term medicines for other chronic conditions using the 4-item Morisky Medication Adherence (MMAS) Scale. MMAS scores were dichotomised into adherent/non-adherent. The Beliefs about Medicines Questionnaires (BMQ) was used to assess patients' beliefs about the long-term medicines. The BMQ-Specific has two scales (necessity and concern) with five questions each that uses a 5-point Likert scale. Internal consistency within BMQ scales was measured with Cronbach's and their association with adherence was assessed with t-Student tests, using SPSS 20.0. Results: We included 126 patients (80.4% male, mean age 49.0}8.3). The mean of long-term medicines was 2.9}2.0. The percentage of non-adherent patients was 54.0%. 63.5% of patients had AIDS, that showed statistically significant relationship with non-adherence. Concerns were negatively related to self-reported adherence (14.6}5.7 vs. 12.1}6.1; p=0.019). No relationship between adherence and necessity was found (17.3}5.6 vs. 18.8}4.4; p=0.188). Internal consistency for BMQ-Specific was high (Cronbach's =0.724). Conclusion: Higher concerns are associated with higher self-reported adherence to long-term medicines in HIV infected-patients